Effects of genotypes, terrain, and irrigation on oil palm yield, and leaf and rachis nutrient concentrations - Lee, Chin Tui (2014)
Foliar analysis is the most common diagnostic tool used to determine the nutritional status of oil palm. Thus the fertilizer requirements of palms are then inferred from these results. In Malaysia, most of the oil palm nutritional research works and their optimal leaf concentrations references were derived from DxP AVROS planting materials. The objective of this study was to evaluate the effects of different oil palm origins, subjected to irrigation and terrain on oil palm yield, leaf, rachis nutrient concentrations and contents over 8 years covering of two periods of yielding assessment i.e ascending and prime stage. An experiment was laid out on palms planted in 1999 at the Tun Razak Centre for Agricultural Services, Jerantut, Pahang, Malaysia (3° 52' 55" North, 102° 43' 41" East) to evaluate the selected genotypes under irrigation and terrain conditions. Results over 8 years on the variations of leaf and rachis nutrient concentrations detected in four clonal oil palm genotypes from different origins i.e. AVROS, Yangambi, La Me and NIFOR and two D×P hybrid Yangambi which were planted on terraced and non-terraced fields subjected to irrigated and non-irrigated conditions were studied. Results clearly showed that rainfall pattern had a great influence on leaf nutrient concentrations and oil yield. Non irrigated palms during ascending yielding stage subjected to uneven rainfall distribution, had higher leaf nutrient concentrations as compared to irrigated palms especially on leaf K and Mg (by 10%) but with lower oil yield (by 13.6%). However, palms grown in the non-terraced area yielded almost 9% higher compared to those planted on terraced areas. The former also have higher leaf Mg and B concentrations which are 10% higher. As the palms reached the prime yielding stage and with good evenly distributed rainfall over time, the effects of terrain and irrigation had been nullified on both yield and foliar nutrient concentrations except for some of the nutrient elements. However, there are marked differences in term of both foliar and rachis nutrient contents among the genotype studied which is attributed to the distinct differences in petiole cross section. Obviously genotypes have a great significant influence on foliar nutrient concentrations and contents for both period of yielding phases. The present study indicated that the high yielding genotypes, D×P Yangambi-DQ 8 consistently showed 15%-20% lower leaf K concentration than the clonal materials of AVROS-A122. Despite the lower leaf K concentration of the former, it retained relatively higher leaf and rachis K contents. It appears therefore that leaf concentration alone is not an adequate method to evaluate the nutritional status of the palms. Incorporation of leaf nutrient contents as well as the rachis nutrient concentrations and contents are certainly useful for better assessment. The present study revealed that fresh fruit bunch (FFB) productions were not significantly different between the genotypes tested, but the oil to bunch ratio (O:B) of the high yielding genotypes remain higher than the standard control (Yangambi D×P, SC3), resulting in a 14-17.5% higher oil yield and 6.1-13.5% more of total economic product (TEP) at the prime yielding phase. Monitoring the leaf cations (K, Ca and Mg) concentrations and contents over 12 years strongly revealed that the high yielding genotypes (Yangambi-Y103, AVROS-A122, and Yangambi-DQ8), had moderate to high leaf nutrient concentrations and consistently recorded higher total leaf cations (TLC) throughout this study and vice-versa for the poorer yielding palms (Yangambi-SC3 and NIFOR-N144). The correlation studies between leaf nutrient concentrations and oil yield components showed that leaf Ca and Mg concentrations are strongly correlated to oil to bunch (O:B) ratio, oil yield and TEP. The results of this study are useful for developing new strategies on oil palm nutrition and breeding programme.